The Effect of Self-Defense Laws on Firearm Use Among Criminal Offenders - D'Alessio, Stewart J. (Crime & delinquency, 2023)
Criminal violence frequently increases within jurisdictions following the implementation of self-defense laws. One explanation for this finding is a firearm amplification effect, whereby criminal offenders increasingly use firearms as a direct response to the amplified threat engendered by citizens. Using longitudinal data drawn from the National Incident-Based Reporting System for 95 cities situated in 15 states, we investigate whether the passing of a stand your ground or castle doctrine law amplifies the likelihood of gun use by criminal offenders. Results from a panel analysis show a marked rise in gun use among criminal offenders following the imposition of both types of self-defense laws. These findings furnish empirical support for the firearm amplification thesis.